Translanguaging as a Resource for Understanding Agricultural Technology in Online ESP Forums - Mutiaraningrum, Ira; Abdurahman, Nur Hafiz; Mahendra, Made Wahyu; Nugroho, Arif; Lestari, Sri (Inspiring: English Education Journal, 2026)
In English for Specific Purposes (ESP) contexts, students are required to understand disciplinary knowledge. In a multilingual classroom, multiple linguistic resources should be allowed to support meaning-making. This study examines how vocational students mobilize translanguaging as a resource for technological sense-making in online ESP learning. Employing a case study, this study focuses on the depth of meaning rather than linguistic frequency or learning outcomes. This study utilized an online discussion forum in Google Classroom to retrieve data from comments and replies from 5th-semester students of the Agricultural Mechanical Engineering Study Program for analysis. Students in this study discuss future agricultural machines they want to build to solve agricultural problems in Sambas Regency. Data were analysed using a thematic discourse-oriented approach through a translanguaging lens. This study reveals that translanguaging was used to (1) explain machine concepts and technical functions, (2) link technology with the needs of the Sambas community, (3) show critical evaluation and awareness of technological limitations, (4) build agreement and collaboration, and (5) express Humour and engagement in online forums. Overall, the study highlights translanguaging as a resource that enables ESP students to make sense of technological ideas through community-oriented technological discourse.